2020
DOI: 10.4102/ajod.v9i0.713
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of working-age adults with aphasia regarding social participation

Abstract: Background Working-age adults with aphasia experience difficulties in social participation, specifically fulfilling social roles and reintegrating into communities. Literature regarding social participation of people with aphasia (PWA) is predominantly based on studies conducted in high-income countries (HIC), limiting generalisability of findings. Perspectives of social participation are influenced by person, place and cultural background warranting investigation in heterogeneous low- and middle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
1
5
0
2
Order By: Relevance
“…In addition to health education, participants appear to rely on their faith during challenging times. Corroborated by other studies, individuals with ABI also mentioned their belief being an important aspect of the recovery process (Karpa et al 2020;Masuku & Khoza-Shangase 2018;Souchon et al 2020). Faith and spirituality were the centre of most of participants' motivation and recovery.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In addition to health education, participants appear to rely on their faith during challenging times. Corroborated by other studies, individuals with ABI also mentioned their belief being an important aspect of the recovery process (Karpa et al 2020;Masuku & Khoza-Shangase 2018;Souchon et al 2020). Faith and spirituality were the centre of most of participants' motivation and recovery.…”
Section: Discussionmentioning
confidence: 55%
“…Although this study consisted of a small sample of 12 individuals, it yielded clinically relevant findings that could be useful for HCP during the acute stage of recovery. Livedexperiences post-discharge have been widely explored, but there is limited research focusing on personal experiences onemonth post-discharge from acute hospitalisation in settings such as South Africa (Souchon et al 2020;van Zyl et al 2019).…”
Section: Limitations Of Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Since all participants with aphasia were actively engaged in aphasia communication support groups, they could anticipate the value of communication partners as part of the research team. The recruitment of communication partners and facilitators such as healthcare students and trained volunteers [42][43][44] is warranted to avoid the risk of being tokenistic within the team. It is suggested that potential patient partners with aphasia be recruited from aphasia communication groups, as they are familiar with communication partner practices, are acquainted with group interactions and are more likely to express their individual needs and views during the research process.…”
Section: Differences Between Pwa and Sswoamentioning
confidence: 99%
“…Since all participants with aphasia were actively engaged in aphasia communication support groups, they could anticipate the value of communication partners as part of the research team. The recruitment of communication partners and facilitators such as healthcare students and trained volunteers[42,43,44] is warranted to avoid the risk of being tokenistic within the team. It is suggested that potential patient partners with aphasia be recruited from aphasia communication groups, as they are familiar with communication partner practices, are acquainted with group interactions and are more likely to express their individual needs and views during the research process.People with aphasia also advocated for various communication facilitators under technological support to enhance the conventional methods of engagement such as speech recognition software, technological aids etc.…”
mentioning
confidence: 99%